Analisis Nilai-Nilai Moral dalam Lirik Lagu Daerah Nias “Ae Halödo Paci dan Lato-Lato” Karya Markus Halawa - Sukardi Hulu; Miseri Cordias Palamarta Gulo; Boy Damai Putra Zega; Noveri Amal Jaya Harefa (Journal on Education, 2024)
The purpose of the research is to describe the meaning and moral values contained in the lyrics of Nias folk songs "Ae Halõdo Paci Dan Lato-Lato" by Markus Halawa. The method used in this research is qualitative method. The data collection stage is using primary data and literature study. After collecting data, the next step is the data analysis stage, namely reduction, data presentation, and conclusions. Then the data is reviewed descriptively and the presentation of the results of data analysis is presented in the form of descriptions of words by providing explanations about the lyrics of Nias folk songs "Ae Halödo Paci and Lato-Lato" by Markus Halawa. The results of the study indicate that there are three types of moral aspects, namely (1) Human relationships with God, namely Help; (2) Human relationships with themselves, namely Honest, Remembering, Strong, Confident, Promising, Sincere, Sad, Steadfast, Accepting Reality, and Hoping; (3) Human relationships with others, namely comforting, begging, believing, advice, honesty with circumstances, and messages.